Retinal ganglion cell function after repeated intravitreal injections of ranibizumab in patients with age-related macular degeneration - Nishimura T (Dove Medical Press, 2012)
Tomoharu Nishimura, Shigeki Machida, Tomomi Harada, Daijiro KurosakaDepartment of Ophthalmology, Iwate Medical University School of Medicine, Morioka, Iwate, JapanBackground: The purpose of this study was to evaluate the safety of intravitreal ranibizumab injection in patients with age-related macular degeneration.Materials and methods: We examined retinal ganglion cell function using the photopic negative response of the electroretinogram (ERG) in patients with age-related macular degeneration (AMD) treated with intravitreal injections of ranibizumab. We studied 32 eyes of 32 patients with AMD and aged 50–84 years with a mean of 71 years. An intravitreal ranibizumab injection was given three times at monthly intervals. Additional injections were given according to an optical coherence tomography-guided variable dosing regimen. ERG recordings were made before treatment (baseline) and at 3, 6, 9, and 12 months postoperatively. Full-field cone ERGs were elicited by red stimuli on a blue background. The focal macular ERGs were elicited by a 15 degree white stimulus spot centered on the macular region. We measured the amplitudes of the a and b waves, oscillatory potentials, and the photopic negative response of the full-field cone and focal macular ERGs.Results: Visual acuity was significantly better than the baseline acuity, and macular thickness was significantly reduced after the intravitreal injections of ranibizumab. The amplitudes and implicit times of each wave of the full-field cone ERGs were not significantly changed after intravitreal ranibizumab injections. However, the amplitudes of each wave of the focal macular ERGs were increased after the injections. The implicit times of the a and b waves of the focal macular ERGs were significantly shortened after intravitreal injections of ranibizumab. The ratio of the full-field and focal photopic negative response/b-wave amplitude was not significantly changed after the injections.Conclusion: The amplitudes of the focal macular ERGs, including the photopic negative response improved after repeated intravitreal ranibizumab injections, accompanied by a recovery of visual acuity and macular structure. The results of the full-field cone ERGs indicate that retinal ganglion cell function was not altered by repeated intravitreal ranibizumab injection.Keywords: age-related macular degeneration, retinal ganglion cell, photopic negative response, electroretinogram, ranibizumab